Disruptive Innovation and the “Penguin Effect” – The Review of Theory - Kalina BOKWA (Communications of International Proceedings, 2022)
This review article was written to introduce and integrate knowledge in the field of disruptive innovation and the phenomenon called the "penguin effect" that appears in the early phase of diffusion of a new solution. The paper is theoretical and exploratory and presents key concepts from a new research perspective. The described connections indicate that breaking the resistance to changes in different participants of the process of adopting disruptive innovations is a serious challenge for subjects trying to launch a new standard in the market. This paper can provide a good theoretical background for further empirical studies.
Keywords: disruptive innovation; diffusion of innovation; commercialization; penguin effect